2019
DOI: 10.1182/bloodadvances.2019000134
|View full text |Cite
|
Sign up to set email alerts
|

PTCy ameliorates GVHD by restoring regulatory and effector T-cell homeostasis in recipients with PD-1 blockade

Abstract: Key Points PD-1 blockade exacerbated GVHD by altering the homeostasis of Tregs and effector T cells after HSCT. PTCy ameliorated GVHD after PD-1 blockade by restoring the homeostatic balance of T-cell subsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 63 publications
(79 reference statements)
0
23
0
Order By: Relevance
“…Importantly, in the current study, PTCy reduced the percentages of Tregs; however, we did not assess splenic Treg numbers, which is an important indicator of immune function. PTCy can increase Treg number in allogeneic mouse models of GVHD [54], but there are limited data in humanized mice. We have previously observed human Tregs in humanized NSG mice with GVHD [31,38,49,[55][56][57][58]; however, PTCy is the first treatment in our laboratory to impact these cells in this model.…”
Section: Ptcy Reduces Gvhd In a Humanized Mouse Modelmentioning
confidence: 99%
“…Importantly, in the current study, PTCy reduced the percentages of Tregs; however, we did not assess splenic Treg numbers, which is an important indicator of immune function. PTCy can increase Treg number in allogeneic mouse models of GVHD [54], but there are limited data in humanized mice. We have previously observed human Tregs in humanized NSG mice with GVHD [31,38,49,[55][56][57][58]; however, PTCy is the first treatment in our laboratory to impact these cells in this model.…”
Section: Ptcy Reduces Gvhd In a Humanized Mouse Modelmentioning
confidence: 99%
“…They found that inhibited PD-1 signaling led to increased and enhanced expansion of CD4 + T cells and unfortunately, Treg cells were unable to support the expansion due to increased apoptosis, resulting in deficiencies in the immune recovery, allowing for development of severe GVHD. Using PTCY on day +3 after transplantation in mice, it was noted that CD4 + T cell populations were decreased with increased Treg populations in the first 2 weeks compared with mice that did not receive PTCY, allowing for a well-balanced immune reconstitution and less GVHD [15]. This study provided insight in how PTCY may be beneficial as a method of GVHD prophylaxis in patients who received prior PD-1 blockade.…”
Section: Acute Gvhd After Transplant In Mds Patientmentioning
confidence: 79%
“…Subsequently, high-dose, single agent post-transplant cyclophosphamide (PTCY) was found to be effective as GVHD prophylaxis and is now standardly used, especially in the setting of haplo-identical [14]. More recently, Ikegawa et al investigated the mechanism of PD-1 blockade in GVHD and how PTCY may impact this process in murine models [15]. They found that inhibited PD-1 signaling led to increased and enhanced expansion of CD4 + T cells and unfortunately, Treg cells were unable to support the expansion due to increased apoptosis, resulting in deficiencies in the immune recovery, allowing for development of severe GVHD.…”
Section: Acute Gvhd After Transplant In Mds Patientmentioning
confidence: 99%
“…*P < 0.05, **P < 0.01, ***P < 0.001. (13,32,33). Regulatory T cells (Tregs), as well as transforming growth factor-b (TGF-b) and IL-10, are known to have important inhibitory functions in CD4 + T-cell proliferation (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…As an important component of the immune system, CD4 + T cells play an indispensable role in resisting foreign pathogens and mediate the development of autoimmunity ( 30 , 31 ). Abnormal CD4 + T-cell proliferation has been implicated in the development of various diseases including peripheral T-cell proliferative diseases/lymphomas, inflammatory/infection diseases, graft-versus-host disease and autoimmune diseases ( 13 , 32 , 33 ). Regulatory T cells (Tregs), as well as transforming growth factor-β (TGF-β) and IL-10, are known to have important inhibitory functions in CD4 + T-cell proliferation ( 34 – 36 ).…”
Section: Discussionmentioning
confidence: 99%